Evaluating the relative value of intraoperative aberrometry versus current formulas for toric IOL sphere, cylinder, and orientation planning. Issue 10 (October 2019) - Solomon, Kerry D.; Sandoval, Helga P.; Potvin, Richard
Abstract : Purpose : To retrospectively review toric intraocular lens (IOL) outcomes and compare actual results to those expected from preoperative calculations and intraoperative aberrometry (IA) in normal eyes. Setting : Carolina Eyecare Physicians, Mt. Pleasant, South Carolina, USA. Design : Retrospective data review of earlier clinical trial data. Methods : Toric IOL planning data and results were obtained from two previous clinical studies of normal eyes receiving toric IOL implants. Back‐calculation techniques were used to estimate expected residual refractive sphere and cylinder for preoperative and IA calculations. Results : Toric IOL planning data and clinical outcomes for 132 eyes receiving two different toric IOLs were analyzed. The mean spherical equivalent refractions expected with preoperative planning and IA were not statistically significantly different ( P = .44), but a higher percentage of eyes within ±0.50 D of the intended spherical refraction was expected with preoperative calculations ( P = .05). The mean expected residual refractive astigmatism based on preoperative calculations was significantly lower than for IA ( P < .001), with more eyes expected to have 0.50 D or less of residual refractive astigmatism. Conclusion : The use of current‐generation formulas for sphere power and toric IOL planning in normal eyes seems sufficient to produce clinical outcomes with toric IOLs that are as good or better than those achieved using IA.